Value choices in a mixed economy of care: How politics shapes the implementation of complex social policies. (25th January 2018) - Nevile, Ann; Kay, Adrian; Carey, Gemma
Abstract: While social and public policy studies recognize the diversity of actors and processes occurring in the implementation of policy and the organization of public service delivery, analysis of the role of value pluralism in implementation remains underdeveloped. This article contributes to a more nuanced understanding of the relationship between value pluralism and organizational responses to value conflict by exploring the effect of politics on the value choices of senior public servants involved in the design and implementation of Australia's National Disability Insurance Scheme. Our analysis shows that politics may play an essential role in facilitating implementation of a complex social policy that contains a number of incommensurable values because successful politics allows these incommensurable values to co‐exist and adaption to take place, thereby avoiding organizational dysfunction.